2023
DOI: 10.1248/bpb.b22-00098
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Peptide Esculentin-1a(1–21)NH<sub>2</sub> Stimulates Wound Healing by Promoting Angiogenesis through the PI3K/AKT Pathway

Abstract: Delayed wound healing is a persistent medical problem mainly caused by decreased angiogenesis. Esculentin-1a(1-21)NH2 [Esc-1a(1-21)NH2], has broadspectrum antibacterial properties which comes from frog skins. It has shown promise as a treatment for wound healing. However, its effects on angiogenesis as well as the mechanism by which esc-1a(1-21)NH2 enhanced wound healing remained unclear. In this study, we analyzed the structural properties and biocompatibility of esc-1a(1-21)NH2 and evaluated its effect on wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…There was epidermal growth factor receptor (EGFR)-mediated activation as well as the involvement of MMP-9 metalloprotease in the Esc-peptide-mediated migration of bronchial epithelial cells [38]. Recently, a paper highlighted the in vivo wound healing activity of the N-terminal acetylated form of Esc(1-21) in a full-thickness excision mouse model [39]. The peptide was able to accelerate wound closure when locally administered at 100 µM, once a day.…”
Section: Discussionmentioning
confidence: 99%
“…There was epidermal growth factor receptor (EGFR)-mediated activation as well as the involvement of MMP-9 metalloprotease in the Esc-peptide-mediated migration of bronchial epithelial cells [38]. Recently, a paper highlighted the in vivo wound healing activity of the N-terminal acetylated form of Esc(1-21) in a full-thickness excision mouse model [39]. The peptide was able to accelerate wound closure when locally administered at 100 µM, once a day.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of Esc(1-21)-1c in encouraging wound healing was further supported by the fluorescein staining results in mice, which showed that at certain doses, it considerably decreased the corneal epithelial wound area [ 60 ]. Esculentin-1a(1-21)A further research by Hu et al (2023) found that NH2 accelerated wound healing by increasing collagen accumulation and angiogenesis, as evidenced by increased PCNA and CD31 expression [ 63 ]. Esculentin-1a(1-21)NH2's angiogenic activity was demonstrated in vitro by increasing cell migration and proliferation in HUVECs; this finding was connected to the activation of the PI3K/AKT pathway [ 63 ].…”
Section: Reviewmentioning
confidence: 99%
“…Esculentin-1a(1-21)A further research by Hu et al (2023) found that NH2 accelerated wound healing by increasing collagen accumulation and angiogenesis, as evidenced by increased PCNA and CD31 expression [ 63 ]. Esculentin-1a(1-21)NH2's angiogenic activity was demonstrated in vitro by increasing cell migration and proliferation in HUVECs; this finding was connected to the activation of the PI3K/AKT pathway [ 63 ].…”
Section: Reviewmentioning
confidence: 99%
“…In most cases, this la er is an enzyme, and its mutations make it easier for the microbes to became resistant to conventional antibiotics that would no longer be able to recognize their specific and single target once modified [41]. Notably, apart from displaying antimicrobial activity by direct killing of microbes, some AMPs do have immunomodulatory properties that indirectly contribute to the pathogens' clearance of the host by recruiting inflammatory cells to the site of infection, by stimulating immune cell differentiation, LPS neutralization [42], suppression of proinflammatory cytokine release [43], and promotion of wound healing [44][45][46]. This is the reason for referring to these molecules as host defense peptides [33], and the models that have been proposed to explain the effect of AMPs on mammalian cells mainly rely on their direct or indirect interaction with membrane receptors of host cells [32].…”
Section: Antimicrobial Peptides (Amps)mentioning
confidence: 99%